2000
DOI: 10.1074/jbc.m003011200
|View full text |Cite
|
Sign up to set email alerts
|

Modification by Arachidonic Acid of Extracellular Adenosine Metabolism and Neuromodulatory Action in the Rat Hippocampus

Abstract: Adenosine and arachidonate (AA) fulfil opposite modulatory roles, arachidonate facilitating and adenosine inhibiting cellular responses. To understand if there is an inter-play between these two neuromodulatory systems, we investigated the effect of AA on extracellular adenosine metabolism in hippocampal nerve terminals. AA (30 M) facilitated by 67% adenosine evoked release and by 45% ATP evoked release. These effects were not significantly modified upon blockade of lipooxygenase or cyclooxygenase and were att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
37
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 57 publications
1
37
0
Order By: Relevance
“…Note that in purified nerve terminals, which only account for 1%Y2% of the volume of more integrated preparations [129], spatial restrains are decreased and it is the only preparation where it has been demonstrated that ecto-5 0 -nucleotidase was the predominant enzymatic activity responsible for the formation of extracellular adenosine from adenine nucleotides [130]. Thus, in nerve terminals, a,b-methylene ADP is able to decrease the formation of extracellular adenosine [107,108,112,117,118].…”
Section: Generation Of Extracellular Adenosinementioning
confidence: 99%
See 1 more Smart Citation
“…Note that in purified nerve terminals, which only account for 1%Y2% of the volume of more integrated preparations [129], spatial restrains are decreased and it is the only preparation where it has been demonstrated that ecto-5 0 -nucleotidase was the predominant enzymatic activity responsible for the formation of extracellular adenosine from adenine nucleotides [130]. Thus, in nerve terminals, a,b-methylene ADP is able to decrease the formation of extracellular adenosine [107,108,112,117,118].…”
Section: Generation Of Extracellular Adenosinementioning
confidence: 99%
“…Two main mechanisms have been identified in nerve terminals for the generation of extracellular adenosine: one is based on the release of adenosine as such through bi-directional non-concentrative (or equilibrative) nucleoside transporters [106]. In fact, inhibition of equilibrative nucleoside transporters can actually decrease the extracellular levels of adenosine in nerve terminals [107,108], in accordance with a build-up of extracellular adenosine involving its release through equilibrative nucleoside transporters in this particular compartment of the brain. The second mechanism for the extracellular build-up of adenosine is its formation from released ATP, after its extracellular catabolism by ecto-nucleotidases (reviewed in [109]).…”
Section: Generation Of Extracellular Adenosinementioning
confidence: 99%
“…Although this is the most widely accepted hypothesis for the build-up of extracellular adenosine, it has only received episodic experimental confirmation (e.g. Cunha et al, 2000;MacDonald and White, 1985). Oddly, the effect of pharmacologically manipulating these nucleoside transporters is an increase of the extracellular levels of adenosine implying that their role is to take-up rather than release adenosine (see Fredholm et al, 2005).…”
Section: Source Of Endogenous Extracellular Adenosinementioning
confidence: 99%
“…In central nervous system (CNS) synapses like in the hippocampus, ATP can act as a neurotransmitter [10,11] and the release of ATP is enriched in presynaptic preparations (cf. [3,6]). In contrast, at motor nerve endings, albeit the extracellular levels of ATP are also increased on stimulation of nerve afferents [16,17,19], there seems to be a considerably larger contribution of post-synaptically released adenine nucleotides [5,19].…”
mentioning
confidence: 99%
“…refs. [3,6]). But the relevant question from the functional point of view is what might be the role of extracellular ATP in the control of neuromuscular transmission.…”
mentioning
confidence: 99%